2002
DOI: 10.1124/jpet.301.2.747
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Eosinophilia in a Murine Model of Allergic Inflammation Is Attenuated by Small Molecule α4β1 Antagonists

Abstract: Inhibition of ␣4␤1/vascular cell adhesion molecule-1 (VCAM-1) interactions have therapeutic potential in treating allergic airway disease because of the importance of these adhesion molecules in the trafficking of eosinophils, lymphocytes, and monocytes. We examined several small molecule inhibitors of ␣4␤1/VCAM-1 interactions with in vitro potencies (IC 50 values) ranging from 0.52 nM (CP-664511; 3-The same compounds were evaluated in vivo using a murine model of ovalbumin-induced pulmonary eosinophilia. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…administration of bilirubin blocks the influx of leukocytes into the lungs of mice with OVA-induced asthma. It has previously been shown that Abs to ␣ 4 integrins or VCAM-1 inhibit the recruitment of eosinophils and lymphocytes into the airways of OVA-sensitized and OVA-challenged mice (34,35). Our finding that bilirubin treatment has identical effects on OVA-induced leukocyte recruitment is consistent with a mechanism of action that involves the disruption of VCAM-1 signaling.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…administration of bilirubin blocks the influx of leukocytes into the lungs of mice with OVA-induced asthma. It has previously been shown that Abs to ␣ 4 integrins or VCAM-1 inhibit the recruitment of eosinophils and lymphocytes into the airways of OVA-sensitized and OVA-challenged mice (34,35). Our finding that bilirubin treatment has identical effects on OVA-induced leukocyte recruitment is consistent with a mechanism of action that involves the disruption of VCAM-1 signaling.…”
Section: Discussionsupporting
confidence: 79%
“…10). Because, in this model, both eosinophil and lymphocyte migration into the lungs have been shown to be VCAM-1-dependent (34,35), our data are consistent with the hypothesis that bilirubin blocks pulmonary leukocyte infiltration by inhibiting VCAM-1 signaling.…”
Section: Effect Of Bilirubin On Allergen-induced Airway Inflammationsupporting
confidence: 79%
See 2 more Smart Citations
“…To date, targeting of ␣ 4 ␤ 1 with synthetic antagonists has been examined in mouse models of lung inflammation/asthma (43,44) and experimental autoimmune encephalomyelitis/MS (45,46) with predominantly beneficial results. However, to our knowledge, no small molecule antagonists specific to ␣ 4 ␤ 1 have been tested so far for treatment in an animal model of an infectious disease.…”
Section: Yme Disease Caused By Three Genospecies Of the Spirochetementioning
confidence: 99%